PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SDN 032 KUALU KECAMATAN TAMBANG - Hasan Basri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
The problem in this research is found in Indonesian subjects that of the 30 students with KKM 75, which has already reached KKM as many as 15 people (41.7%), while that has not reached the KKM as many as 21 students (58.3%). The situation was caused by the teacher in explaining the lesson Indonesian still using a model of lectures and familiarize students to memorize, so that students can develop their ideas. The problems of this study as follows: Is the learning model application role playing can improve learning outcomes Indonesian fifth grade students of SDN 032 Kualu Kecamatan Tambang? This study aims to improve learning outcomes Indonesian grade students of SDN 032 Kualu Kecamatan Tambang through the application of learning models role playing. This research was conducted one month from the month of April 2015. The research was conducted 2 cycles, with each cycle consisting of two meetings as well as twice daily tests. Classroom action research in order to succeed, the researchers set the stage that action planning, action, observation and reflection. Based on the research results, it could be concluded that the activity of teachers in learning implementation role playing, in the first cycle average teacher activity amounted to 62.50% in the category of less pretty, and the activities of teachers in the second cycle of 84.72% in both categories once. Thus there is increased activity of teachers by 22.22% from the first cycle to the second cycle. The average activity of students in the first cycle the percentage of student activity in learning tends to increase. At the first meeting with the average student activity that is 61.25% with the category enough. At the second meeting increased by an average of student activity that is 81.25% with the category enough. The average increase in the activity of the students from the first cycle to the second cycle of 20.00%. The class classically considered complete when a class has achieved a score of 85% of the amount due or to KKM 75 then the class is said to be completed (90.00%). From the above shows that the application of learning models can improve outcomes role playing learning Indonesian grade students of SDN 032 Kualu Kecamatan Tambang, it can be concluded that the hypothesis is accepted as true action.